2020
DOI: 10.1007/s11239-020-02319-w
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding risk in patients with venous thromboembolic events treated with new oral anticoagulants

Abstract: New oral anticoagulants (NOACs) is the preferred treatment in secondary prophylaxis of venous thromboembolic events (VTE). The aim of this study was to investigate possible risk factors associated with major bleeding in VTE-patients treated with NOACs. In this retrospective register-based study we screened the Swedish anticoagulation register Auricula (during 2012.01.01–2017.12.31) to find patients and used other national registers for outcomes. Primary endpoint was major bleeding defined as bleeding leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Among the 18,219 patients, 938 had a major bleeding and the rate of major bleeding was 6.62 (95% CI 6.19-7.06) per 100 treatment years. Renal failure was associated with a higher risk of major bleeding in this study, but the finding was not confirmed in multivariate analysis [46]. Another study, conducted by Bixby,Shaikh et al,compared 197 adult KTRs who received either warfarin or NOACs due to VTE or AF.…”
Section: Safetycontrasting
confidence: 57%
“…Among the 18,219 patients, 938 had a major bleeding and the rate of major bleeding was 6.62 (95% CI 6.19-7.06) per 100 treatment years. Renal failure was associated with a higher risk of major bleeding in this study, but the finding was not confirmed in multivariate analysis [46]. Another study, conducted by Bixby,Shaikh et al,compared 197 adult KTRs who received either warfarin or NOACs due to VTE or AF.…”
Section: Safetycontrasting
confidence: 57%
“…Consistent with known risk factors and clinical trials [ 3 , 9 ], our data showed that IRs of intracranial, gastrointestinal and other bleeding events were higher in patients aged 75 years or older. Older age was also found to be an independent risk factor for major bleeding in a study of Swedish national registries (normalized hazard ratio [95% CI]: 1.38 [1.27–1.50]) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other risk factors for bleeding were collected including drug interactions increasing apixaban exposure/area under the curve (amiodarone, diltiazem, verapamil, cyclosporine, azole antifungals, dronedarone, clarithromycin, erythromycin), alcohol use, thrombocytopenia (<150/µL), increased bilirubin (>1.2 mg/dL) or liver function tests (>3 times upper limit of normal), uncontrolled blood pressure (>160 mmHg systolic blood pressure), active cancer undergoing treatment, history of cirrhosis, ischemic stroke, chronic obstructive pulmonary disease (COPD), peptic ulcer bleeding (PUD), or prior bleeding event. 17,18 Baseline serum creatinine was defined as the most recent documented lab value in the chart within the prior year or as documented by physician progress notes, and the cause of AKI was also determined by physician documentation. Patients were followed from the time of admission through hospital discharge for outcome evaluation.…”
Section: Data Collectionmentioning
confidence: 99%